Ghana’s herbal medicine industry: prospects, challenges and ways forward from a developing country perspective - Asase, Alex (Frontiers in Pharmacology, 2023)
The herbal medicine industry is one of the fastest growing industries in the world. However, no detailed assessments have been undertaken on how to achieve the benefits of this industry for developing countries. This study examined the herbal medicine industry in Ghana, with a particular focus on its prospects, challenges and ways forward. The prospects of the medicinal plant trade are huge, and include reducing the national health budget, being a source of foreign and domestic income, as well as creation of employment and poverty reduction. However, the industry is currently inundated with several challenges, such as registration of herbal medicine products and practitioners, a lack of clinical trials for herbal products, standards and quality control issues, shortage of raw plant materials for production, and insufficient scientific research to support traditional claims on the pharmacological effects of medicinal plants. I propose a number of interventions to address these challenges: increased government support, capacity building initiatives, improved regulation of herbal medicines, application of modern technology in the manufacturing of herbal products, large-scale cultivation of medicinal plants, and improved packaging and branding for herbal medicines. Both the national government and the private sector have crucial roles to deliver in the development of the herbal medicine industry in a country like Ghana.